2001
DOI: 10.1139/y00-087
|View full text |Cite
|
Sign up to set email alerts
|

Fourier-transform infrared spectroscopy: a pharmacotoxicologic tool for in vivo monitoring radical aggression

Abstract: Among the physico-chemical methods that can be used to investigate induced peroxidation in living cells, Fourier transform infrared (FT-IR) spectroscopy appears to be a valuable technique as it is non-destructive and sensitive for monitoring changes in the vibrational spectra of samples. We examined microsomal fractions from rat liver and brain by FT-IR to study the effect of radical aggression induced in vivo by carbon tetrachloride (CCl4). The length of the acyl chains was increased as a consequence of perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…The CH 2 asymmetric stretching band~2927 cm −1 and the symmetric CH 2 stretching band~2849 cm −1 provide information about lipid acyl chain flexibility (an order/disorder of lipids) [26]. This change in intensity and the shift in the frequency asymmetric CH 2 stretching band indicate a change in lipid disorder in the membranes of tissues [13]. In our study, it is observed from Fig.…”
Section: Principal Component Analysissupporting
confidence: 59%
See 1 more Smart Citation
“…The CH 2 asymmetric stretching band~2927 cm −1 and the symmetric CH 2 stretching band~2849 cm −1 provide information about lipid acyl chain flexibility (an order/disorder of lipids) [26]. This change in intensity and the shift in the frequency asymmetric CH 2 stretching band indicate a change in lipid disorder in the membranes of tissues [13]. In our study, it is observed from Fig.…”
Section: Principal Component Analysissupporting
confidence: 59%
“…The ratio of the intensity of absorption of the bands between I 2960 /I 2873 could be utilized as the principal measure of quantity of methyl groups in protein fibers [12]. Moreover, the ratio of I 2924 /I 2853 can be used to monitor the state of biological membranes [13]. As seen from Fig.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…It is also clearly observed that lipid droplets were increased in liver sections treated by CCl 4 and examined by electron microscope. These findings were in parallel to biochemical plasma cholesterol analyses which showed a high significant increase of plasma cholesterol [57]. Verapamil produced the most significant reduction in cholesterol level.…”
Section: Histochemical Discussionsupporting
confidence: 74%
“…A survey of the literature reveled that there are a few methods for diosmin determination in pharmaceutical formulations or biological fluids. These methods include voltammetry, [11] thin-layer chromatography, [12] high performance liquid chromatography (HPLC), [13,14] Fourier transform infrared spectrometry, [15,16] and spectrodensitometry. [17] The methods based on modern instrumental techniques are sensitive, i.e., by the HPLC method, 50 ng diosmin per injection could be detected.…”
Section: Introductionmentioning
confidence: 99%